Stress–strain model for high-strength concrete tied columns under concentric compression. (August 2021) - Koksal, H.O.; Erdogan, A.
Abstract: Providing accurate constitutive stress–strain relationships for confined concrete can increase the reliability of the moment curvature (MC) analyses in the displacement-based seismic design of reinforced concrete (RC) columns. This paper presents a new stress–strain model for high-strength concrete (HSC) tied square columns which exhibit a more brittle behavior than normal strength concrete (NSC) members. Introducing the concept of least confined volume in the damage localization zone at the middle of the concrete core, a new approach is developed for the confinement stress distribution of lateral ties. In order to determine the lateral stresses acting on the vertical surfaces of the least confined volume, the effective confinement stresses are reduced considering the tie configuration. The peak strength and the ductility of the column should therefore be calculated for the confined concrete in this region. A concrete failure criterion applicable to multi-axial compression due to the reduced confinement stresses in two orthogonal directions, is then used to determine the ultimate strength of HSC columns. Moreover, plotting the compression meridian of the failure criterion, a simple and design-oriented formula is proposed for the ultimate strength of HSC tied columns. The validity of the proposed approach and the performances of two well-known analytical models are verified against the test results of eighty-six HSC columns from five different experimental studies for both the axial stress–strain behavior and the ultimate strength. Besides, the implementation of the concept of the reduced confinement stress in the Mander's model leads to a significant improvement in its capability of predicting the triaxial strength of HSC.